The Identification of "Other Especially Serious Circumstances" in the Crime of Obtaining Loans by Fraud - He, Huiling (International Journal of Social Sciences and Public Administration, 2025)
Following the amendments introduced by the Criminal Law Amendment (XI), "other especially serious circumstances" has become the sole circumstantial element for sentencing gradation in the crime of obtaining loans by fraud. "Other especially serious circumstances" constitutes an aggravating circumstance within the framework of aggravated offenses by circumstances. Its determination must comply with the legal principles governing basic offenses and aggravated offenses, and it must be premised on the act having already "caused significant losses." Acts that have not "caused significant losses" should not be directly classified as having "other especially serious circumstances." Simultaneously, equivalence must be considered between "causing especially significant losses" and "other especially serious circumstances." Only conduct presenting a risk equivalent to "causing especially significant losses" can be identified as "other especially serious circumstances." In concrete identification, the focus should be on the severity of the conduct itself, combined with the systemic position of the aggravating circumstance. Factors such as amount or frequency should no longer serve as singular criteria; they must be assessed alongside the actual economic losses caused by the conduct.